The Relationship Between Family Support And The Level Of Independence Among Post-Stroke Patients At Tabanan Regional General Hospital - Ni Kadek Septia Dewi; Ni Luh Putu Thrisna Dewi Dewi; Niken Ayu Merna Eka Sari (Jurnal Medicare, 2026)
Stroke is a major cause of disability that can reduce patients’ level of independence in performing activities of daily living. Post-stroke conditions require continuous support, particularly from family members as the closest support system. Optimal family support is expected to assist the recovery process and enhance patients’ independence. This study aimed to analyze the relationship between family support and the level of independence among post-stroke patients at Tabanan Regional General Hospital. This study employed a correlational analytic design with a cross-sectional approach. The sample consisted of 78 post-stroke patients selected using a total sampling technique. Data were collected using a family support questionnaire and a patient independence questionnaire, and were analyzed using the Spearman correlation test. The results showed that the majority of respondents received moderate family support, accounting for 41 respondents (52.6%). Most post-stroke patients had a moderate level of dependency, with 38 respondents (48.7%). The Spearman correlation analysis indicated a significant relationship between family support and the level of independence among post-stroke patients, with a correlation coefficient of r = 0.562 and a p-value = 0.000 (p < 0.05). Better family support was associated with a higher level of patient independence. The conclusion of this study demonstrates that there is a significant relationship between family support and the level of independence among post-stroke patients. Therefore, family involvement should be optimized as an integral part of post-stroke care and rehabilitation programs